IMPLEMENTASI PENDEKATAN STUDENT ACTIVE LEARNING BERBASIS PROJECT WORK UNTUK MENINGKATKAN KERJA SAMA PESERTA DIDIK - Aisa Winda Fatmawati; Nurhidayati; Rizkia Pangestika, Rintis (STKIP Subang, 2026)
This research emerged from the low level of student cooperation and learning outcomes on the topic of magnetism in Grade V at SD Negeri 1 Jangkrikan. Teacher-centered teaching methods have resulted in limited student participation and engagement in learning activities. The purpose of this study is to describe the implementation of a Student Active Learning approach based on Project Work and to determine the improvement in students’ cooperative character after the approach is applied. This study belongs to the category of Classroom Action Research (CAR) using the Kemmis & McTaggart model, conducted in two cycles involving 19 students in the 2025/2026 academic year. Data collection techniques included interviews, observations, tests, and field notes, which were analyzed descriptively using both quantitative and qualitative approaches. The research findings indicate an improvement in student cooperation from 57.89% in the pre-cycle to 85% at the end of Cycle II. Student learning outcomes also showed significant progress. The conclusion of this study is that the Project Work–based Student Active Learning approach is effective in improving students’ cooperation as well as their learning outcomes. This research contributes an innovative and relevant active learning strategy that can help enhance the quality of education in elementary schools.